The Skincubator: A Novel Incubator for Skin-to-Skin Care (SSC) of Premature Neonates, Enables SSC within Humidified Environment and May Improve Thermoregulation during SSC - Nitzan, Itamar; Kasirer, Yair; Mimouni, Francis B.; Kagan, Tehilla; Bin Nun, Alona; Weiss, Tali B.; White, Robert D.; Hammerman, Cathy (American Journal of Perinatology, 2025)
This study aimed to assess thermoregulation and humidity within the Skincubator—a novel, wearable skin-to-skin incubator designed to attach to the caregiver.Preterm neonates (PN; born between 24 and 33 weeks gestational age [GA]) received skin-to-skin care (SSC) either via the Skincubator or traditional SSC (t-SSC) with continuous axillary temperature monitoring.Twenty PN were enrolled in the study and treated in the Skincubator. One couple who consented to Skincubator care during delivery subsequently revoked their consent and the baby was excluded from further analysis. Fifty-four paired sessions of Skincubator and t-SCC were performed and compared for 19 babies. The average GA was 29 weeks (range: 26–32), the average weight was −1,296 ± 271 g, and the average day of life was 5 ± 2. The temperature drop after transfer to Skincubator care was smaller than in t-SSC (0.2°C [0.2–0.3] vs. 0.4°C [0.3–0.6]; Wilcoxon's signed rank test [WSRT], p < 0.001). The average hypothermia time per session was a median (25th–75th%) of 8.2 minutes (0–9) for Skincubator, compared to 27.8 minutes (0–56) for t-SSC, respectively (WSRT, p = 0.002). No baby had moderate hypothermia (35.5–35.9°C) during Skincubator care as compared with eight babies who experienced moderate hypothermia during t-SSC (Fisher's exact test p = 0.003). The average Skincubator humidity was 85 ± 7% and was above 70% during 93% of the time.Skincubator SSC was superior to t-SSC in maintaining PN temperature while also maintaining an optimally humidified environment. The Skincubator may promote early SSC in very and extremely PN. (Trial registration number MOH_2021–12–13_010470 registration date 24/10/21.)
Keywords: skin-to-skin care; kangaroo mother care; preterm neonates; thermoregulation